Faktor-Faktor yang Menyebabkan Klien Drop Out dari Program Rehabilitasi Rawat Jalan di Klinik Pratama BNN di Wilayah Jawa Barat - Mirianty, Widiana; Rofii, Muhammad Syaroni, Mr.; Iskandar, Anang (UI Scholars Hub, 2021)
Identifying the risk for early dropout of the program may help to improve the retention in treatment, thereby also having an impact on better recovery outcome (Basu et al., 2017). Drug trafficking and narcotics abuse destructed young generation who are potential in developing country, are a threat to stability of national security. This study aims to identify and understand the factors that cause client dropout from the outpatient program at Primary Clinic of BNN in West Java. The result found that dropout at Primary Clinic of BNN in West Java was influenced by the stability of social condition factor, rehabilitation history, and motivation to change. Treatment related factors in the form of consideration for the client’s needs also have an impact to drop out even not significantly. Keywords: Drop out, Rehabilitation, Outpatient Program